Dampak Problem Based Learning Terhadap Kemampuan Penalaran Matematis Siswa Kelas XI IPA SMAN 7 Padang Tahun Pelajaran 2019/2020 - HAFIZA . (Jurnal Edukasi dan Penelitian Matematika, 2020)
Based on observation at class XI IPA SMAN 7 Padang, it was found that students’ mathematical reasoning abilities were low. One of the reasons was the learning implementation was not optimal for training and improving mathematical reasoning skill well. The effort that can be used was implementing PBL model. The purpose of this study was to determine and describe wheter the mathematical reasoning ability that the learning applied PBL model was better than applying direct learning model. This type of research was quasy experiment with Randomized Control-Group Only Design. The population was students of class XI IPA SMA Negeri 7 Padang  while class XI IPA 4 and XI IPA 5 as a sample. The instrument used in this research was a mathematical reasoning ability test with essay questions. The results showed that mathematical reasoning ability by applying PBL model is better than mathematical reasoning ability by applying direct learning model.Keywords – Problem Based Learning (PBL), reasoning skill, Mathematics